Mediation: Process and practice in Hong Kong - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2010)
Mediation Process and Practice in Hong Kong draws upon diverse traditional and contemporary practices to offer a layered and nuanced view of mediation to reflect the internationality of Hong Kong. The chapters are lucidly written and structured with useful illustrations, diagrams and figures that visually enhance and assist the reader to consolidate the wealth of information shared by the author. Part one, ‘Process’, explores the principles, values, models, process elements and skills of mediation, and introduces the Mediation Bridge for the first time in Hong Kong. The Mediation Bridge is a metaphor for mediation which visually guides the reader through the mediation process. Part two, ‘Practice’ covers developments of mediation practice, areas of application, the laws applicable and the role of technology